Alternative indictment in the Peruvian Criminal Procedural Code: Challenges and difficulties - Fernández Vásquez, Marcelo Alejandro (2023)
The alternative indictment is regulated in the current Peruvian Criminal Procedural Code of 2004 as part of the discretionary and inherent powers of the Government Attorney General’s Office as the operator of the criminal action and head of the investigation. Its use has increased in complex and hypercomplex criminal proceedings, in which the representative of the Government Attorney General’s Office applies more than one charge for the fact being prosecuted, creating issues in its use and application, both for the Government Attorney General’s Office and for the defense. In this sense, this research will analyze and delve into the nature and purposes of alternative indictment, the infringement or not of the rights of the defendant when using this option, its use in personal preliminary injunctions, among other aspects.